The Celsr3-Kif2a axis directs neuronal migration in the postnatal brain. (January 2022) - Hakanen, Janne; Parmentier, Nicolas; Sommacal, Leonie; Garcia-Sanchez, Dario; Aittaleb, Mohamed; Vertommen, Didier; Zhou, Libing; Ruiz-Reig, Nuria; Tissir, Fadel
Highlights: Celsr3 specifies the directionality and regulates velocity of migration. Celsr3-deficient neuroblasts exhibit exuberant branching. Celsr3 regulates the growth and stability of microtubules. Celsr3 interacts physically with Kif2a and their deficiencies cause similar phenotypes. Abstract: The tangential migration of immature neurons in the postnatal brain involves consecutive migration cycles and depends on constant remodeling of the cell cytoskeleton, particularly in the leading process (LP). Despite the identification of several proteins with permissive and empowering functions, the mechanisms that specify the direction of migration remain largely unknown. Here, we report that planar cell polarity protein Celsr3 orients neuroblasts migration from the subventricular zone (SVZ) to olfactory bulb (OB). In Celsr3 -forebrain conditional knockout mice, neuroblasts loose directionality and few can reach the OB. Celsr3-deficient neuroblasts exhibit aberrant branching of LP, de novo LP formation, and decreased growth rate of microtubules (MT). Mechanistically, we show that Celsr3 interacts physically with Kif2a, a MT depolymerizing protein and that conditional inactivation of Kif2a in the forebrain recapitulates the Celsr3 knockout phenotype. Our findings provide evidence that Celsr3 and Kif2a cooperatively specify the directionality of neuroblasts tangential migration in the postnatal brain.